Travmatski izpahi kolena - Macura, Marko (Medicinski razgledi, 2006)
Traumatic knee dislocation is a medical emergency. It is associated with extensive damage of all elements of the knee joint, among which injury of the popliteal blood vessels presents a serious threat to the limb. Despite the fact that many features of this type of injury are known, there is still a high percentage of above-the-knee amputations, mainly due to failure to recognize and properly treat such injuries. The common peroneal nerve injury is permanent in fifty percent of cases. The earliest possible repair of damaged knee ligaments and joint capsule, which if at all possible should be done during the same surgical procedure as popliteal artery repair, proved to be the best way to avoid rigid or unstable knee and accomplish the most functional joint.
Keywords: diagnostika; koleno; poškodbe; izpah; anatomija